PENGARUH KOMUNIKASI DAN MOTIVASI TERHADAP KUALITAS PELAYANAN PEGAWAI PADA PUSKESMAS TALISE KOTA PALU - REZKI, REZKI (JURNAL ILMU MANAJEMEN UNIVERSITAS TADULAKO, 2020)
The aim of this study is to find out and analyze the effect of communication and motivation on the quality of service employees in Talise City of Palu City. The sample used in this study was 73 employees at the Thalise Health Center in Palu City. The method used in this study is multiple linear regression. Based on the t-test conducted and the results of the regression analysis, the communication and motivation variables have a positive and significant effect on the quality of employee services at the Thalise Health Center in Palu City. Determination test shows R-square value of 76.5% which means that service quality variables are influenced by independent variables namely communication and motivation while the remaining 23.5% is influenced by other variables not examined in this study